Electrochemical and ESR Study on Pt‐TiOx/C Electrocatalysts with Enhanced Activity for ORR1. Issue 2 (22nd July 2013) - Sakai, Go; Arai, Tatsuya; Matsumoto, Toshiaki; Ogawa, Tetsuya; Yamada, Mayumi; Sekizawa, Koshi; Taniguchi, Takumi
<x xml:space="preserve">Abstract</x> Pt‐TiO x /C electrocatalysts possess specific activities for the oxygen reduction reaction of about 1.5 times higher than that of conventional Pt/C. Electron‐spin resonance spectra suggest that the specific activity of Pt‐TiOx/C is related to the amount of ESR‐active species.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>